The Way of the Rod: The Functions of Beating in Late Medieval Pedagogy. - Parsons, Ben (Modern Philology, 2015)
The article explores the functions of beating as punishment in schools in the late Middle Ages. Particular focus is given to the rationales developed by late medieval pedagogues, commentators and educational theorists including Aristotle, Plato and Peter John Olivi. It also explores the routine practice of punishment in the medieval classroom,